Functional linkage between research and extension in Veterinary universities - SINHA, SUSHIL KUMAR; CHANDER, MAHESH; KUMAR, SANJAY; VERMA, MED RAM (The Indian Journal of Animal Sciences, 2021)
This ex-post-facto study was carried out to measure the research-extension linkage in veterinary universities of India with the help of a developed index, incorporating 7 major dimensions of functional linkage. Data were collected from 120 respondents comprising of 80 researchers and 40 extensionists sampled from four veterinary universities and linkage strength between the two were computed in terms of Extent of Functional Linkage (EOFL) to categorize them in four classes of linkage strength. The results of the study revealed an unsatisfactory functional research-extension linkage between research and university-extension system. In all the selected veterinary universities, majority of respondents expressed weak to very weak linkage strength for almost all the studied dimensions of linkage.